2023
DOI: 10.7554/elife.83055
|View full text |Cite
|
Sign up to set email alerts
|

Transiently heritable fates and quorum sensing drive early IFN-I response dynamics

Abstract: Type I Interferon (IFN-I)-mediated antiviral responses are central to host defense against viral infections. Crucial is the tight and well-orchestrated control of cellular decision-making leading to the production of IFN-Is. Innovative single-cell approaches revealed that the initiation of IFN-I production is limited to only fractions of 1-3% of the total population, both found in vitro, in vivo, and across cell types, which were thought to be stochastically regulated. To challenge this dogma, we addressed the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The proposed model recapitulates the expected time to production of IFN by early responders, which is in the range of 4-8 h [2,46]. The low fraction of IFN-producing cells is also on par with other estimates indicating that up to a few percent of cells produce interferons, see, e.g., [6,47,48]. As in experiments, the scant sources of IFN, especially at a low MOI, amplify cell population heterogeneity by giving rise to characteristic foci of IFN-activated cells [46].…”
Section: Plos Pathogenssupporting
confidence: 55%
“…The proposed model recapitulates the expected time to production of IFN by early responders, which is in the range of 4-8 h [2,46]. The low fraction of IFN-producing cells is also on par with other estimates indicating that up to a few percent of cells produce interferons, see, e.g., [6,47,48]. As in experiments, the scant sources of IFN, especially at a low MOI, amplify cell population heterogeneity by giving rise to characteristic foci of IFN-activated cells [46].…”
Section: Plos Pathogenssupporting
confidence: 55%
“…Log difference is a reliable method for detecting significant changes at the population level but is likely to miss changes in sub-populations of the cells [34]. We recall that identifying changes in sub-populations is shown to be a key in understanding the early response dynamics [31].…”
Section: Differential Expression For Gene Selectionmentioning
confidence: 99%
“…However, with the single-cell data becoming increasingly more accessible, other differential expression metrics such as earth mover's distance (EMD) and mutual information (MI) are also being investigated as alternatives. EMD specifically is known to perform well in detecting changes in sub-populations and detection of subpopulations is essential in understanding pathogen responses as these responses are typically initiated by a small set of early-responders [31]. [32], [33] are two of the early works that showed that informative genes are reliably extracted using EMD between heterogenous cell classes.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to capture immune secretory behaviors in rather simplified models, population-level studies have suggested highly constrained models, where target gene responses are subjected to tight epigenetic and transcriptional regulation ( 6 8 ). In contrast, at the single-cell level, TLR effector responses exhibit high variability characterized by all-or-nothing cellular decision-making ( 9 15 ). This heterogeneity is thought to reflect complex transcriptional regulation, characterized by dynamic transcription factor signaling ( 16 , 17 ) as well as diverse genomic architecture ( 18 ) and immune quorum sensing/licensing ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%